1996
DOI: 10.1007/bf00785766
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity in a Nigerian paediatric primary care service: a comparison of two screening instruments

Abstract: We evaluated the screening properties of the Children's Behaviour Questionnaire (CBQ) and the Reporting Questionnaire for Children (RQC) in an urban primary care setting in Nigeria. Using various validity indices and the results of Receiver Operating Characteristic analysis, we showed that the two instruments had identical abilities at differentiating children with specific psychiatric disorders from those without. The cut-off threshold for the CBQ in this setting was different from what is commonly reported e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 17 publications
4
29
0
Order By: Relevance
“…This is further supported by the findings that the items that occurred significantly more often in children with conduct disorders and emotional disorders 8 are the items that were extracted in the factor analysis as conduct and emotional factors.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This is further supported by the findings that the items that occurred significantly more often in children with conduct disorders and emotional disorders 8 are the items that were extracted in the factor analysis as conduct and emotional factors.…”
Section: Discussionsupporting
confidence: 55%
“…8 The CBQ was administered in its Yoruba version derived by the iterative back-translation method. Because of the high rate of illiteracy in the population, the questions were read aloud by medical students who had received prior training in the screening process.…”
Section: Methodsmentioning
confidence: 99%
“…4 Early onset bipolar disorder, especially in the adolescent period is associated with more co-morbidity, impairment in functioning and poor quality of life. 5 Despite the high prevalence and enormity of mood disorders among Nigerian children and adolescents 6,7,8 , information is lacking on functioning and factors influencing functioning in children and adolescents with bipolar disorder in this environment.…”
Section: Introductionmentioning
confidence: 99%
“…CBQ is an instrument that has been tested and used in many countries of the world and has been found to be acceptable and valid. 19,21,22 CBQ has two versions, parents (Scale A) and teachers (Scale B). The teachers' version consists of 26-items and parents version 31-items, investigating the child's behaviour at school and at home respectively.…”
mentioning
confidence: 99%
“…In the present study a cut-off of 7 as suggested by a validation study by Omigbodun et al 19 was used. In their study the threshold of 7 on the scale, gave the best trade-off between a high sensitivity and a low false-positive rate.…”
mentioning
confidence: 99%